Annular fuel neutronic analysis. (August 2023) - Luiz Pereira Rebello Júnior, André; Huria, Harish C.; Senra Martinez, Aquilino; da Cruz Gonçalves, Alessandro
Highlights: Neutronic characteristics of the annular fuel were analysed using PARAGON2. The verification and validation process of PARAGON2 for annular fuel geometries. The results showed that PARAGON2 is a viable option for modeling annular fuel. This new fuel design was proposed to increase the power density. Abstract: The annular fuel was proposed to increase the power density while keeping or improving the safety margins, given the considerably lower surface heat flux and lower fuel temperature than conventional solid fuel. In this paper, neutronic characteristics of this new fuel design were analysed using the new transport code of the Westinghouse, called PARAGON2, using Ultra-Fine Energy Mesh Library for multi-group cross section calculations. The bibliographical review showed there is a lack of deterministic transport codes capable to model such fuel with acceptable accuracy, because the equivalence relations for heterogeneous resonance integrals adopted in the standard codes were formulated only for solid cylindrical rods. Therefore, the main objective of this paper is to perform neutronic analysis for annular fuel using PARAGON2, evaluating the use of Ultra-Fine Energy Mesh Library to eliminate resonance self-shielding calculation. The results of this paper analysed the power distributions, the ratio of U-238 capture rate to U-235 fission rate and behaviour of the infinite multiplication factor for annular fuel and compared with the Monte Carlo code MCNP.